Using PIGE for analysis of boron carbide of received by CVD method - Levenets, V.; Omelnyk, A.; Shchur, A.; Shirokov, B. (Вопросы атомной науки и техники, 2008)
The method PIGE was used for determination of stoichiometry and isotopic content of boron carbide in one measurement. The optimal conditions of experimental measurement were determined. The possibility was shown of obtaining of boron carbide enriched according to boron using CVD-method.